Gamma-ray and high-energy X-ray detection with large-area scintillating crystals: A hands-on review - Bonesini, Maurizio (Frontiers in Detector Science and Technology, 2025)
Detection of photons with scintillating inorganic crystals in the high-energy range (>0.1 MeV) will be discussed, making a comparison with other available methods. Energy resolutions up to 2% at 662 keV and fast decay time of the order of 20 ns are within reach, with the introduction of Ce-doped crystals in place of alkali halide ones. Development is underway for the production of non-hygroscopic scintillating crystals, such as PrLuAg and Ce: GAAG. At the end of this review, examples of experimental devices based on scintillating inorganic crystals will be discussed. Practical hands-on experience is emphasized at the expense of a more comprehensive description of all available and possible options. Detectors’ construction details and consequences of the different choices will be discussed. Emphasis will be put on the LaBr3: Ce-based detectors that are the present “golden standard” in gamma ray spectroscopy. The focus of this review will be on photon detection in the high-energy region: mainly 0.1–2 MeV, including both gamma rays and high-energy X-rays, even if many considerations may be applied to the detection of low-energy X-rays.